Styles and Strategies of Leadership during the Alaskan Native Land Claims Movement: 1959-71 - Ervin, Alexander M. (Anthropologica, 2022)
Following statehood, Alaskan native peoples were involved in a political struggle to define and maintain land rights in the face of massive developmental schemes and actual projects. At the beginning of Alaska statehood, local, rural, grass-roots native movements emerged. These were later replaced by a unified, highly disciplined, and sophisticated lobbying effort by a small core of elite natives operating through the Alaska Federation of Natives. This movement was remark able because of the skills of its leaders in identifying and managing important political, economic, and normative pressure points, and in establishing useful networks of political alliance in the complex American political culture of interest group activities. Although now controversial, the resulting federal legislation in the form of the Alaska Native Claims Settlement Act of 1971 was the most innovative approach to native land claims for its time.